The subjective right to physical culture and sport in the system of constitutional human rights in Ukraine - Opanasiuk, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
The article provides a comprehensive constitutional and legal analysis of the subjective right to physical culture and sport within the system of constitutional human rights in Ukraine. It is substantiated that the right to physical culture and sport has an independent meaning, while being closely interconnected with such fundamental rights as the right to health care, the right to rest, the right to education and the right to free development of the personality. The provisions of the Constitution of Ukraine, national legislation and international acts in the field of human rights that directly or indirectly enshrine the right of a person to engage in physical culture and sport have been analyzed. It has been established that the right to physical culture and sport is an independent subjective constitutional right, which is simultaneously integrated into the system of social and cultural human rights. Its legal nature is based on the provisions of the Constitution of Ukraine, in particular Articles 3, 49 and 50, as well as on special legislation in the field of physical culture and sport. This right combines an individual legal aspect, which provides an opportunity for a person to independently implement physical culture and sport, and a social and legal aspect, which provides for the state’s obligations to create conditions for mass, accessible and inclusive sports. The content, signs and features of the implementation of the subjective right to physical culture and sport are determined, as well as the range of its subjects and the state’s obligations to create appropriate conditions for its implementation. The social significance of the specified right in the context of modern challenges is emphasized, considering the need to ensure the health of the nation, social integration and inclusion. The conclusion is made on the expediency of further improving the constitutional and legal mechanism for guaranteeing and implementing the right to physical culture and sport in Ukraine.